1996
DOI: 10.1001/archpsyc.1996.01830030039007
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Follow-up of Naltrexone and Psychotherapy for Alcohol Dependence

Abstract: Some but not all of the benefits resulting from short-term naltrexone treatment persist after discontinuation of treatment. The findings suggest that continued treatment with naltrexone may be beneficial for some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(122 citation statements)
references
References 12 publications
4
110
0
8
Order By: Relevance
“…therapeutic efficacy of NTX in treating alcoholism (O'Malley et al, 1992(O'Malley et al, , 1996Volpicelli et al, 1992Volpicelli et al, , 1997Anton et al, 1999;Chick et al, 2000;Johnson and Ait-Daoud, 2000;Heinala et al, 2001;Krystal et al, 2001;Morris et al, 2001;Guardia et al, 2002), identifying factors that predict therapeutic response to NTX is a critical goal of alcoholism research. Although the cognitive effects of acute and chronic NTX may differ, recent data supports equivalent or greater efficacy of acute NTX dosing, relative to daily maintenance, in reducing excessive alcohol intake (Hernandez-Avila et al, 2006).…”
Section: Discussion Ntx Effects On Impulsive Choicementioning
confidence: 99%
“…therapeutic efficacy of NTX in treating alcoholism (O'Malley et al, 1992(O'Malley et al, , 1996Volpicelli et al, 1992Volpicelli et al, , 1997Anton et al, 1999;Chick et al, 2000;Johnson and Ait-Daoud, 2000;Heinala et al, 2001;Krystal et al, 2001;Morris et al, 2001;Guardia et al, 2002), identifying factors that predict therapeutic response to NTX is a critical goal of alcoholism research. Although the cognitive effects of acute and chronic NTX may differ, recent data supports equivalent or greater efficacy of acute NTX dosing, relative to daily maintenance, in reducing excessive alcohol intake (Hernandez-Avila et al, 2006).…”
Section: Discussion Ntx Effects On Impulsive Choicementioning
confidence: 99%
“…Clinical studies also demonstrate that treatment of detoxified alcoholics with naltrexone reduces both the frequency of drinking and the relapse to heavy drinking (Volpicelli et al, 1992;O'Malley et al, 1992O'Malley et al, , 1996O'Malley et al, , 2002. Also, in a clinical laboratory setting, it was shown that non-treatmentseeking alcoholics treated with naltrexone consume less alcohol when presented in a laboratory setting than do placebo treatment subjects.…”
Section: Introductionmentioning
confidence: 97%
“…71 Other studies have also shown naltrexone to reduce the reinforcing effects and to increase the unpleasant (i.e., sedative) properties of initial alcohol consumption. 72,73 O'Malley et al 74 found that the beneficial effects of naltrexone diminished gradually during a posttreatment follow-up period. Further, abstinence during treatment strongly predicted whether subjects met criteria for alcohol abuse or dependence at a 6-month posttreatment follow-up.…”
Section: Treatment Of Alcohol Dependencementioning
confidence: 98%